Cost-effectiveness of Randomized Study of Laparoscopic Versus Open Bilateral Inguinal Hernia Repair. Issue 5 (November 2018) - Ielpo, Benedetto; Nuñez-Alfonsel, Javier; Duran, Hipolito; Diaz, Eduardo; Fabra, Isabel; Caruso, Riccardo; Malavé, Luis; Ferri, Valentina; Barzola, Ernesto; Quijano, Yolanda; Vicente, Emilio
Abstract : Objective: The aim of this study is to compare the clinical and cost-effective outcomes of the open Lichtenstein repair (OL) and laparoscopic trans-abdominal preperitoneal (TAPP) repair for bilateral inguinal hernias. Summary Background Data: A cost-effective analysis of laparoscopic versus open inguinal hernia repair is still not well addressed, especially regarding bilateral hernia. Methods: This is a clinical and cost-effectiveness analysis within a randomized prospective study conducted at Sanchinarro University Hospital. Cases of primary, reducible bilateral inguinal hernia were included and randomized using a simple randomization program. The outcome parameters included surgical and postoperative costs, quality adjusted life years (QALY), and incremental cost per QALY gained or the incremental cost effectiveness ratio. Results: Between March 2013 and January 2017, 165 patients were enrolled in this study (81 of them underwent TAPP and 84 OL). The TAPP procedure had less early postoperative pain ( P = 0.037), a shorter length of stay ( P = 0.001), and fewer postoperative complications ( P = 0.002) when compared with the OL approach. The overall cost of TAPP procedure was higher compared with the OL cost (1, 683.93[Euro sign] vs 1192.83[Euro sign], P = 0.027). The mean QALYs at 1 year for TAPP (0.8094) was higher than that associated with OL (0.6765) ( P = 0.018). At a willingness-to-pay threshold of 20, 000 [Euro sign] and 30, 000 [Euro sign], there was a 95.38% and 97.96% probability that TAPP was more cost-effective relative to OL. Conclusions: The TAPP procedure for bilateral inguinal hernia appears to be more cost-effective compared with OL.